Some properties for integro-differential operator defined by a fractional formal - Abdulnaby, Z.E.; Ibrahim, R.W.; Kılıçman, A. (SpringerOpen, 2016)
Recently, the study of the fractional formal (operators, polynomials and classes of special functions) has been increased. This study not only in mathematics but extended to another topics. In this effort, we investigate a generalized integro-differential operator Jm(z) defined by a fractional formal (fractional differential operator) and study some its geometric properties by employing it in new subclasses of analytic univalent functions.